How Far Artificial Intelligence influenced Mu'allim, Murabbi, and Mudarris? Transhumanism and Diffusion of Innovation Theory's Perspective - Thoriquttyas, Titis; Rohmawati, Nita (Universitas Muhammadiyah Surakarta, 2024)
The rapid growth of Artificial Intelligence (AI) has begun to change many elements of education, including Islamic religious education. Traditionally, Mu'allim, Murabbi, and Mudarris have played important roles in teaching, ethics, and spiritual guidance. However, little is known about the impact of AI on the shifting existence of these terminologies. This research delves into the impact of AI on the responsibilities and perspectives of Mu'allim, Murabbi, and Mudarris, especially through the lens of transhumanism and the diffusion of innovation theory. This study uses qualitative methods to examine data, exploring the variations in AI integration in Islamic education across diverse cultural and regional backgrounds while also recognizing the specific best practices and challenges in each setting. The research seeks to close the gap in understanding between contemporary technology and Islamic educational customs by examining the evolving responsibilities of educators in the age of artificial intelligence. The findings raise significant issues regarding the preservation of human-centered values in religious education while also highlighting the potential of AI to improve educational methods. This study bridges the gap between traditional educational philosophies and technology breakthroughs, contributing to the increasing body of literature on AI in education and providing insightful information for Islamic studies researchers.